STRAIN AND COMPETENCE CONTRAST ESTIMATION FROM FOLD SHAPE - Schmalholz S.M.; Podladchikov Y.Y. (My University, 2001)
A new method to estimate strain and competence contrast from natural fold shapes is developed and verified by analogue and numerical experiments. Strain is estimated relative to the nucleation amplitude, AN, which is the fold amplitude when the amplification velocities caused by kinematic layer thickening and dynamic folding are identical. AN is defined as the initial amplitude corresponding to zero strain because folding at amplitudes smaller than AN is dominantly by kinematic layer thickening. For amplitudes larger than AN, estimates of strain and competence contrast are contoured in thickness-to-wavelength (H/λ) and amplitude-to-wavelength (A/λ) space. These quantities can be measured for any observed fold shape. Contour maps are constructed using existing linear theories of folding, a new nonlinear theory of folding and numerical simulations, all for single-layer folding. The method represents a significant improvement to the arc length method. The strain estimation method is applied to folds in viscous (Newtonian), power-law (non-Newtonian) and viscoelastic layers. Also, strain partitioning in fold trains is investigated. Strain partitioning refers to the difference in strain accommodated by individual folds in the fold train and by the whole fold train. Fold trains within layers exhibiting viscous and viscoelastic rheology show different characteristic strain partitioning patterns. Strain partitioning patterns of natural fold trains can be used to assess the rheological behaviour during fold initiation.
Keywords: STRAIN ESTIMATION; FOLDING; FOLD SHAPE; COMPETENCE CONTRAST; STRAIN PARTITIONING; FOLD TRAINS; Tonian; Precambrian::Proterozoic::Neoproterozoic::Tonian; Докембрий::Протерозой::Неопротерозойская::То́ний